1982
DOI: 10.1128/aem.44.4.790-800.1982
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stages in the Biodegradation of the Surfactant Sodium Dodecyltriethoxy Sulfate by Pseudomonas sp. Strain DES1

Abstract: The biodegradation of the surfactant sodium dodecyltriethoxy sulfate by Pseudomonas sp., strain DES1 (isolated from activated sludge plant effluent) has been studied. Growth of the organism when the 35S-labeled surfactant was present as the sole source of carbon and energy led to the appearance in the culture fluid of five 35S-labeled organic metabolites. These have been identified as mono-, di-, and triethylene glycol monosulfates (major metabolites) and acetic acid 2-(ethoxy sulfate) and acetic acid 2-(dieth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…not involve hydrolytic cleavage of the sulphate group but rather cleavage of the ether linkage to provide a long-chain alcohol (subsequently biodegraded by mechanisms analogous to the PAS case) and a series of ethylene glycol sulphates which are in turn further metabolised (12). There is at present no evidence for the mechanism by which biodegradation of SAS occurs though, by analogy with other surfactants, initial w-oxidation followed by P-oxidation of the alkyl chain might be expected to occur.…”
Section: P a Gilbert And R Pettigrewmentioning
confidence: 99%
“…not involve hydrolytic cleavage of the sulphate group but rather cleavage of the ether linkage to provide a long-chain alcohol (subsequently biodegraded by mechanisms analogous to the PAS case) and a series of ethylene glycol sulphates which are in turn further metabolised (12). There is at present no evidence for the mechanism by which biodegradation of SAS occurs though, by analogy with other surfactants, initial w-oxidation followed by P-oxidation of the alkyl chain might be expected to occur.…”
Section: P a Gilbert And R Pettigrewmentioning
confidence: 99%
“…Metabolite analysis in Pseudomonas sp. strain Des1 (38,39), Pseudomonas sp. strain SC25A (40), and P. nitroreducens (41) revealed that degradation starts with cleavage of the ether bonds, but cleavage of the sulfate ester bond has also been shown to occur concomitantly to ether cleavage in some of these strains (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…A zymogram analysis of alkylsulfatase was also conducted using the whole protein content of S15. Fresh protein aliquots were used for native Polyacrylamide gel Analysis, followed by incubation of gel at 30°C in a solution containing 10 mmol l À1 SDS and 20 mmol l À1 BaCl 2 in 20 mmol l À1 Tris-HCl, pH 7Á8 (Hales et al 1982).…”
Section: Alkylsulfatase Assaymentioning
confidence: 99%
“…The plasmid DNA profiles of parent microbe and transformants were analyzed by agarose gel electrophoresis. The SDS degradation ability of S15 and transformant at protein level was finally confirmed by alkylsulfatase assay (Ellis et al 2002) and zymogram analysis (Hales et al 1982). Biosurfactant production ability of transformant was further analyzed by inoculating them on SCM plates and incubating at 30°C for 2-3 days.…”
Section: Analysis Of Plasmid Associated Sds Degradation and Biosurfacmentioning
confidence: 99%